PENGARUH PROBLEM BASED LEARNING BERBANTUAN MEDIA PEMBELAJARAN QUIZWHIZZER BERBASIS DIGITAL TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF SISWA PADA PEMBELAJARAN IPA KELAS V MATERI MENGENAL ORGAN PENCERNAAN MANUSIA - Fini Dardanili; Rosmiati; Triman Juniarso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students' poor reflective thinking abilities, ineffective use of digital learning resources, and slow learning processes in science classes in Sidoarjo City's primary schools prompted this study. The purpose of this research is to find out how fifth graders' reflective thinking abilities on the human digestive system fared when taught utilizing the problem-based learning approach with the use of the digital learning tool Quizwhizzer. Two experimental groups using the problem-based learning paradigm are part of this descriptive quantitative study's quasi-experimental approach. The results show that the pupils' ability to think reflectively has significantly improved. In experimental class 1, the t-value was 22.19, which is greater than the t-table value of 2.06, and in experimental class 2, the t-value was 36.60, which is also greater than the t-table value of 2.06. Experimental classes 1 and 2 both have N-Gain values of 0.73 and 0.78, respectively. Therefore, it has been demonstrated that the digital learning tool Quizwhizzer helps fifth graders improve their reflective thinking abilities.